2021
DOI: 10.1155/2021/5547911
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-Derived Exosomal microRNA-130a Serves as a Noninvasive Biomarker for Diagnosis and Prognosis of Oral Squamous Cell Carcinoma

Abstract: Exosomal microRNAs (miRNAs) are considered as potential stable biomarkers in many types of human cancer, but investigations of plasma-derived exosomal miRNAs in oral squamous cell carcinoma (OSCC) are still lacking. The aim of this study is to evaluate the diagnostic and prognostic values of exosomal miR-130a in OSCC patients. Exosomes were isolated from plasma samples which were collected from 184 OSCC patients before surgery and 196 healthy individuals. Primary OSCC and paired adjacent noncancerous tissues w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…Previous studies showed that the composition and cargo of TEX correlates with disease stage, tumor activity and progression, assigning them great potential as biomarkers for HNSCC (11,(17)(18)(19)(20). Additionally, exosomal miRNAs from plasma or serum show promising disease-discriminatory potential in oral (21) and laryngeal cancer (22).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that the composition and cargo of TEX correlates with disease stage, tumor activity and progression, assigning them great potential as biomarkers for HNSCC (11,(17)(18)(19)(20). Additionally, exosomal miRNAs from plasma or serum show promising disease-discriminatory potential in oral (21) and laryngeal cancer (22).…”
Section: Introductionmentioning
confidence: 99%
“…The influence analysis and outlier detection identified several outlier individual studies. After excluding seven outliers ( 34 , 38 , 41 , 47 , 48 ), the I 2 for heterogeneity decreased both in sensitivity (from 91.49% to 84.30%) and specificity (from 89.17% to 84.31%). However, the overall results showed only minimal changes and were similar to the original ones as the pooled specificity of the overall study increased from 0.76 to 0.78, PLR increased from 3.2 to 3.4, DOR decreased from 9 to 10, and AUC increased from 0.82 to 0.83, while sensitivity and NLR had no changes.…”
Section: Resultsmentioning
confidence: 97%
“…The Exo-miR profiling showed a significant increase in Exo-miR-130a-3p in patients with relapse. MiR-130a-3p has mainly been described as down-modulated in lung cancer compared to normal lung tissue [ 32 ], but the Exo associated form has been correlated with an unfavorable prognosis in some cancer types [ 33 , 34 ]. This opposite effect is not surprising; indeed, Exo-miRs, as being circulating, can act not only on tumor cells but on immune and stromal cells as well, modifying their functions in a context-dependent manner.…”
Section: Discussionmentioning
confidence: 99%